2023
DOI: 10.1038/s41380-023-02032-z
|View full text |Cite
|
Sign up to set email alerts
|

Reducing default mode network connectivity with mindfulness-based fMRI neurofeedback: a pilot study among adolescents with affective disorder history

Abstract: Adolescents experience alarmingly high rates of major depressive disorder (MDD), however, gold-standard treatments are only effective for ~50% of youth. Accordingly, there is a critical need to develop novel interventions, particularly ones that target neural mechanisms believed to potentiate depressive symptoms. Directly addressing this gap, we developed mindfulness-based fMRI neurofeedback (mbNF) for adolescents that aims to reduce default mode network (DMN) hyperconnectivity, which has been implicated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 93 publications
1
11
0
Order By: Relevance
“…The real-time DMN detection algorithms tested are implemented through proprietary software produced by Resonait Medical Technologies Pty Ltd, fully outlined in [14]. The established method for inferring the DMN states has been the subject of numerous publications [7], [10], [15], [16]. It was applied to the LEMON dataset using the open source OSL-Dynamics toolbox [17].…”
Section: Methodolodgymentioning
confidence: 99%
See 2 more Smart Citations
“…The real-time DMN detection algorithms tested are implemented through proprietary software produced by Resonait Medical Technologies Pty Ltd, fully outlined in [14]. The established method for inferring the DMN states has been the subject of numerous publications [7], [10], [15], [16]. It was applied to the LEMON dataset using the open source OSL-Dynamics toolbox [17].…”
Section: Methodolodgymentioning
confidence: 99%
“…Normalisation of DMN connectivity is theorised to be the mechanism of action of transcranial magnetic stimulation (TMS), a brain stimulation therapy that has proven effective in treating depression [6]. Neurofeedback methods implemented using functional magnetic resonance (fMRI) imaging to target DMN connectivity patterns have also been shown to reduce depressive symptoms in patients [7], [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is a patient-specific parcellation and white matter fiber map for several well-known connectome networks, including the default mode network (DMN), 10,11 optic radiation (OR), 12 and central executive network (CEN). 13-15 The network data were in-turn converted to a set of “burn-in” images where the voxel data containing network parcellation or fiber tracts were set to the maximum voxel value for the data set. One series of burn-in images was created for each connectome network.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Several studies have shown the feasibility of volitional control of DMN activity using functional magnetic resonance imaging (fMRI)-neurofeedback, either defined as a single region (Garrison et al, 2013;Harmelech et al, 2015;G. Zhang et al, 2013), multiple regions (McDonald et al, 2017), or through relative DMN activity, compared to other largescale networks (Kim et al, 2019;J. Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%